Significant response of pulmonary sarcomatoid carcinoma with obstructive atelectasis to treatment with the PD-1 inhibitor camrelizumab combined with transbronchial cryoablation: A case report and literature review - Nian, Jiayun; Zhu, Yong; Fu, Qi; Yang, Guowang; Wang, Xiaomin (Frontiers in Oncology, 2022)
Pulmonary sarcomatoid carcinoma (PSC) is a rare subtype of non-small cell lung cancer with high malignancy and poor prognosis. Chemotherapy or radiotherapy do not usually provide satisfactory results in patients with PSC, especially in those with advanced-stage cancer. Targeted therapy and immunotherapy are more precise therapies that may be effective in the treatment of PSC; however, further research is needed. Here, we present a case of stage III PSC with obstructive atelectasis, which is more challenging and hinders treatment. Treatment with the PD-1 inhibitor camrelizumab and transbronchial cryoablation showed significant clinical efficacy. This type of combined treatment has not been reported previously for PSC. Thus, this case may provide a valuable reference for future clinical practice and research.